Laras Desa: Rancangan Konsep Media Komunitas Pemberdayaan Keluarga - Irfan Dhiya Alaudin; Adi Nur Vianto; Aldoni Pratama Susanto; Fadil Rizqi Pangestu; Giwang Eka Risti; Annis Azhar Suryaningtyas (Jurnal Surya Masyarakat, 2021)
Family Welfare Empowerment (PKK) is a forum for women's involvement in the main development of the family empowerment. However, there are obstacles in the regeneration process. Therefore, the Magelang Regency Government made an innovative program by forming the Millennial Family Welfare Empowerment. One of the goals of the Millennial Family Welfare Empowerment is to implement innovation and accelerate family empowerment activities. This is in line with the role of community media in guarding development for community empowerment. The use of community media has not been widely used as a means of empowering families and communities., as in Tempuran District. Meanwhile, the existence of community media can basically be a channel for delivering information needed by citizens. Become a public discussion forum. As well as helping to reach an agreement to solve the problem. Finally, fostering a spirit of participation in development that focuses on community empowerment. In this study using a Systematic Literature Review (SLR) approach. Those who emphasize the collection of data and information focus on the use of media in the PKK community in Tempuran, Magelang Regency. The result of this research is the creation of “Laras Desa” Community Media, which is inspired by the 10 Main Tasks of the PKK. These 10 main tasks are broken down into main points in the “Laras Desa” content, which includes information on issues of education, health, environment, socio-culture, economy, and entertainment created and needed by partner communities.